2000
DOI: 10.1080/01971520009349542
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method of Electroelution of Individual Protein Bands from SDS Polyacrylamide Gels for Direct Study in Cellular Assays

Abstract: A very simple and effective procedure which allows simultaneous electroelution of separated proteins from SDS polyacrylamide gel into small quantity of elution buffer is described. Elution parameters have been optimized for maximum possible recovery (50-60%). Protein fractions were collected in physiological buffer and an efficient removal of SDS have been obtained, thus fractions collected were suited for direct testing in cell cultures. Method was used to investigate human T-cell responses to purified secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Gel electrophoresis has been used previously to fractionate antigens for study of T cell responses. A handful of studies in the late 80’s, early 90’s [ 46 52 ] and one in 2000 [ 53 ] reported cellular responses to individual components in complex preparations of antigens fractionated by SDS-PAGE. These reports were a logical extension of earlier studies using SDS-PAGE-fractionated antigens as immunogens [ 54 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gel electrophoresis has been used previously to fractionate antigens for study of T cell responses. A handful of studies in the late 80’s, early 90’s [ 46 52 ] and one in 2000 [ 53 ] reported cellular responses to individual components in complex preparations of antigens fractionated by SDS-PAGE. These reports were a logical extension of earlier studies using SDS-PAGE-fractionated antigens as immunogens [ 54 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improved methods were developed later, in which samples were fractionated using 2D gel electrophoresis, followed by electroelution of proteins and dialysis; this fractionation method avoided transfer of proteins to membranes and eliminated the SDS in the sample, rendering protein fractions in a suitable solvent for cellular assays [ 52 , 53 , 58 ]. Bhaskar et al [ 53 ] identified eight antigenic fractions of defined molecular weight but did not report identification of the eluted M. tuberculosis antigens. In our protocol, we used a one-dimension fractionation step, sidestepped transfer to nitrocellulose membranes, and identified targets using proteomic workflows involving in-gel tryptic digestion and LC-MS/MS analysis of tryptic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of electroelution, SDS can be effectively removed during the elution procedure if a SDS-free elution buffer is used (e.g., [9,[13][14][15][16]). In the case of electroelution, SDS can be effectively removed during the elution procedure if a SDS-free elution buffer is used (e.g., [9,[13][14][15][16]).…”
Section: Removal Of Sds and Protein Recoverymentioning
confidence: 99%
“…Berdasarkan hasil optimasi, proses elektroelusi protein target 31 dan 56 kDa berhasil dilakukan dengan menggunakan tegangan listrik 25 V selama 150 menit. Purifikasi protein kemudian dilanjutkan dengan proses dialisis untuk menghilangkan kontaminan yang masih bercampur dengan protein target (Bhaskar et al 2008). Prinsip kerja dialisis adalah pergerakan acak molekul atau partikel di dalam zat pelarut dari larutan dengan konsentrasi tinggi ke larutan dengan konsentrasi yang lebih rendah melalui membran semipermeabel (Haney et al 2013).…”
Section: Purifikasiunclassified